Slope Stability of Civil Construction Waste Landfill at Jardim Chapadão in Bauru-SP - Silva, Nelson Júlio Silveira; Silva, Celso Antonio Donizeti da; Scoton, Edvaldo José (Technical and Scientific Journal Green Cities, 2021)
The occupation process, since 1998, in the municipality of Bauru, in some cases; it occurred inappropriately, with a procedure without any planning and dealing with spaces previously considered adequate for the purpose of supporting the dumping of such inert waste, as well as the possibility of environmental recovery of the place. This work concerns the finalization of the recovery process of the “Jardim Chapadão pit”, in particular the technical and scientific assessment of the stability of the various finished slopes and whose plateaus should receive a layer of vegetation in order to recover part of the local biome. From the tests carried out on the samples collected “in loco”, the results demonstrated an angle of internal friction of 75º, superior to the angle of 45º given as limit for the dry ground in sand and clay type soil. Thus, it is concluded that in the critical profile of the polygonal, the slope presents instability and, therefore, measures are suggested in order to achieve stability and assist in the recovery of the local biome. KEYWORDS: Soil degradation. Recovery of degraded area. Soil occupation.